Microsoft office 2003 - Cable, Sandra (McGraw-Hill Technology Education, 2005)
This text includes features that make learning easy and enjoyable - yet - challenging for learners. The text includes a wide range of learning experiences from activities with one or two commands to simulations and case studies that challenge and sharpen learners' problem-solving skills. This book is ideal for computer courses with learners who have varying abilities and previous computer experiences. The book covers Office 2003 Basics and the Internet, Word, Excel, Access, PowerPoint, Outlook, and Publisher